2015
DOI: 10.3390/md13074344
|View full text |Cite
|
Sign up to set email alerts
|

New α-Glucosidase Inhibitory Triterpenic Acid from Marine Macro Green Alga Codium dwarkense Boergs

Abstract: The marine ecosystem has been a key resource for secondary metabolites with promising biological roles. In the current study, bioassay-guided phytochemical investigations were carried out to assess the presence of enzyme inhibitory chemical constituents from the methanolic extract of marine green alga—Codium dwarkense. The bioactive fractions were further subjected to chromatographic separations, which resulted in the isolation of a new triterpenic acid; dwarkenoic acid (1) and the known sterols; androst-5-en-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…Our results are in accordance with previous studies that analyzed the effect on α-glucosidase of F. vesiculosus ’ fucoidans [ 22 ] with an IC 50 > 50 mg/mL and commercially-available polyphenol extracts [ 49 , 50 ], with IC 50 of 0.604 µg/mL and 5 µg/mL, respectively, when obtained with hot water but further purified with ultrafiltration. Certain molecules from other seaweed species have also been studied for their ability to inhibit α-glucosidase, particularly, a triterpenoid from Padina boergesenii [ 51 ], a triterpenic acid from Codium dwarkense [ 52 ], octaphlorethol A from Ishige foliacea [ 53 ] and crude extracts from Grateloupia elliptica [ 54 ], with IC 50 ’s of <100 µg/mL, 3.31 µg/mL, 109 µg/mL and 20 µg/mL, respectively. However, these compounds were again obtained through extensive purification procedures with organic solvent extraction and column fractionation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accordance with previous studies that analyzed the effect on α-glucosidase of F. vesiculosus ’ fucoidans [ 22 ] with an IC 50 > 50 mg/mL and commercially-available polyphenol extracts [ 49 , 50 ], with IC 50 of 0.604 µg/mL and 5 µg/mL, respectively, when obtained with hot water but further purified with ultrafiltration. Certain molecules from other seaweed species have also been studied for their ability to inhibit α-glucosidase, particularly, a triterpenoid from Padina boergesenii [ 51 ], a triterpenic acid from Codium dwarkense [ 52 ], octaphlorethol A from Ishige foliacea [ 53 ] and crude extracts from Grateloupia elliptica [ 54 ], with IC 50 ’s of <100 µg/mL, 3.31 µg/mL, 109 µg/mL and 20 µg/mL, respectively. However, these compounds were again obtained through extensive purification procedures with organic solvent extraction and column fractionation.…”
Section: Discussionmentioning
confidence: 99%
“…Also reported were diterpenoids, 731-733, an a-tocopheroid 734, a sterol 735 along with 12 known compounds from Caulerpa racemosa 504 and a triterpene acid 736 from Codium dwarkense. 505 The diterpenoid 733 and the a-tocopheroid 734 are the rst natural products to contain the haematinic acid and 3,5dimethylphenoxy motifs respectively.…”
Section: Green Algaementioning
confidence: 99%
“…In this regard, prospects have shown that various terrestrial and aquatic plants possess novel chemical constituents, which could help in inhibiting α-glucosidase activity in diabetic conditions [ 17 ]. Previously, aquatic- and/or marine-derived plants have been reported to provide potent resources for finding α-glucosidase inhibitors, as described by one of our previous communications [ 18 ] and those by other researchers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%